EVALUASI ASET ALOKASI PADA PORTOFOLIO HIGH NETOWRTH WEALTH MANAGEMEN KELUARGA BAPAK ANTON - , Dian Eka Puspitasari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aimed at how to manage a wealth of High Net Worth Individuals by knowing the client profile based on the type of risk-taking, analyzing and evaluating the management of wealth according to the needs of clients and 2 Pillar Wealth Management, and formulate alternative solutions and recommendations based on the type of client risk. This case study uses a client who is willing to provide information about the personal wealth of data, cash flow and some information related to the management of client assets. This type of risk based on the client questionnaire and the the authors make recommendations in accordance with client which is growth and accumulation a client wealth management, asset management . There are two alternative scenarios clients advice on wealth management. The results of the wealth management clients in select on scenario 2 because can increase net cashflow the clien. Recommendations on the scenario 2, asset diversification (, boarding-lodging business, savings, deposits, fixed-income BNP Paribas prima 2 and Simas Danamas, Gold and RD Panin Dana Maksima. Recommendations of the selected clients can improve cash flow net Rp. 1,433,279,000.